Distributional Outcomes of a Decentralized Welfare Program - Galasso, Emanuela (The World Bank, 1999)
April 2000 - Community-level targeting of antipoverty programs is now common. Do local community organizations target the poor better than the central government? In one program in Bangladesh, the answer tends to be yes, but performance varies from village to village. The authors try to explain why. It is common for central governments to delegate authority over the targeting of welfare programs to local community organizations - which may be better informed about who is poor, though possibly less accountable for getting the money to the local poor - while the center retains control over how much goes to each local region. Galasso and Ravallion outline a theoretical model of the interconnected behavior of the various actors in such a setting. The model's information structure provides scope for econometric identification. Applying data for a specific program in Bangladesh, they find that overall targeting was mildly pro-poor, mostly because of successful targeting within villages. But this varied across villages. Although some village characteristics promoted better targeting, these were generally not the same characteristics that attracted resources from the center. Galasso and Ravallion observe that the center's desire for broad geographic coverage appears to have severely constrained the scope for pro-poor village targeting. However, poor villages tended not to be better at reaching their poor. They find some evidence that local institutions matter. The presence of cooperatives for farmers and the landless appears to be associated with more pro-poor program targeting. The presence of recreational clubs has the opposite effect. Sometimes the benefits of decentralized social programs are captured by local elites, depending on the type of spending being decentralized.